Different mechanisms in periventricular and deep white matter hyperintensities in old subjects - Cai, Jinsong; Sun, Jianzhong; Chen, Haiyan; Chen, Ying; Zhou, Ying; Lou, Min; Yu, Risheng (Frontiers in Aging Neuroscience, 2022)
Objective Although multiple pieces of evidence have suggested that there are different mechanisms in periventricular white matter hyperintensities (PWMHs) and deep white matter hyperintensities (DWMHs), the exact mechanism remains uncertain. Methods We reviewed clinical and imaging data of old participants from a local She Ethnic group. We assessed the cerebral blood flow of white matter (WM-CBF) on arterial spin-labeling, deep medullary veins (DMVs) visual score on susceptibility-weighted imaging, and index for diffusion tensor image analysis along the perivascular space (ALPS index), indicating glymphatic function on diffusion tensor imaging. Furthermore, we investigated their relationships with volumes of PWMHs and DWMHs. Results A total of 152 subjects were included, with an average age of 63 ± 8 years old. We found that higher age and history of hypertension were independently related to higher volumes of both PWMHs and DWMHs (all p < 0.05). Lower ALPS index was independently associated with higher PWMHs volumes (β = 0.305, p < 0.001), and this relationship was accounted for by the indirect pathway via DMVs score (β = 0.176, p = 0.017). Both lower ALPS index and WM-CBF were independent risk factors for higher DWMHs volumes (β = −0.146, p = 0.041; β = −0.147, p = 0.036). Conclusions Our study indicated that there were different mechanisms in PWMHs and DWMHs. PWMHs were mainly attributed to the damage of veins due to the dysfunction of the glymphatic pathway, while DWMHs could be affected by both ischemia-hypoperfusion and dysfunction of the glymphatic pathway. Advances in knowledge The relationship between glymphatic dysfunction and PWMHs might be accounted for by the indirect pathway via venous abnormalities, a glymphatic dysfunction, and lower CBF in white matter were independent risk factors for DWMHs.